Presence of kratom in opioid overdose deaths: findings from coroner postmortem toxicological report - Torrico, Tyler; Patel, Kajal; Nikolov, Nicole; Salam, Md. Towhid; Padhy, Ranjit; Weinstein, David (Frontiers in Psychiatry, 2024)
Kratom (Mitragyna speciosa) use in the United States is becoming increasingly popular and its legal status varies widely from state to state. Multiple reports of adverse events associated with kratom use have ranged from liver injury, seizures, psychiatric disturbance, and rarely death.This study investigated coroner autopsy reports from Kern County in California for the year 2020 which included qualitative data on substances from blood toxicological reports. Of the 214 opioidassociated accidental overdoses reported, 4 subjects (1.9%) had mitragynine (kratom) exposure on the autopsy report and were included in the study. We reported available demographic information and comorbid substance findings from the associated autopsy reports.All 4 individuals with mitragynine (kratom) toxicology had accidental opioid overdose deaths noted in autopsy reports. Each subject also had toxicology positive for at least one other substance.Fentanyl was found in 3 (75%) of the cases and suspected to be the primary contributor to opioidrelated deaths in those cases. However, one fatality was without fentanyl, but instead had tested positive for benzodiazepines, cannabis, and other psychiatric medications.